PENGEMBANGAN PERMAINAN TRADISIONAL BOI-BOIAN SEBAGAI MEDIA PEMBELAJARAN PBL UNTUK MENINGKATKAN LITERASI LINGKUNGAN PESERTA DIDIK PADA MATERI USAHA & ENERGI - Gendri Sri Wahyuni; Nurita Apridiana Lestari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Physics learning on the topic of work and energy has great potential to be contextualized through real-life activities and environmental issues. However, current learning practices tend to be abstract, teacher-centered, and have not optimally integrated environmental literacy. This study aims to develop an edutainment-based learning medium utilizing the traditional boi-boi an game integrated with the Problem-Based Learning (PBL) model on the topic of work and energy, as well as to determine the feasibility and implementation of the developed media. This study employed a limited Research and Development (R&D) method by adapting a simplified Borg and Gall development model. The research stages included needs analysis, product design, initial product development, expert validation, product revision, and limited-scale field testing. Validation was conducted by physics content experts and environmental education experts. Limited-scale testing involved four participants to observe the implementation of the module. The results of expert validation indicated that the learning module was categorized as feasible for use with revisions. The results of the limited-scale trial showed that the module could be implemented according to the designed learning scenario and that the boi-boi an game activities could be carried out effectively. Therefore, the edutainment-based learning media utilizing the traditional boi-boi an game integrated with the PBL model is considered feasible on a limited basis for teaching the topic of work and energy and has the potential to support environmental literacy. Further research involving larger-scale trials is required to comprehensively examine the effectiveness of the learning media.